Deletion of aquaporin-4 curtails extracellular glutamate elevation in cortical spreading depression in awake mice - Enger, Rune; Sprengel, Rolf (Cerebral cortex, 2017)
Abstract. Cortical spreading depression (CSD) is a phenomenon that challenges the homeostatic mechanisms on which normal brain function so critically depends.